A late Pleistocene sedimentation in the Indus Fan, Arabian Sea, IODP Site U1457. (17th May 2019) - Kumar, Anil; Dutt, Som; Saraswat, Rajeev; Gupta, Anil Kumar; Clift, Peter D; Pandey, Dhananjai Kumar; Yu, Zhaojie; Kulhanek, Denise K
Abstract: The intensity of turbidite sedimentation over long timescales is driven by sea-level change, tectonically driven rock uplift and climatically modulated sediment delivery rates. This study focuses on understanding the effect of sea-level fluctuations and climatic variability on grain-size variations. The grain size and environmental magnetic parameters of Arabian Sea sediments have been documented using 203 samples, spanning the last 200 ka, obtained from International Ocean Discovery Program (IODP) Site U1457. Grain-size end-member modelling suggests that between ~200 and 130 ka there was an increase in the coarse silt fraction caused by sediment transport following reworking of the Indus Fan and development of deep-sea canyons. The sediment size and enhanced magnetic susceptibility indicate a dominant flux of terrestrial sediments. Sedimentation in the distal Indus Fan at c . 200–130 ka was driven by a drop in sea level that lowered the base level in the Indus and Narmada river systems. The low sea-stand caused incision in the Indus delta, canyons and fan area, which resulted in the transportation of coarser sediment at the drilling site. Magnetic susceptibility and other associated magnetic parameters suggest a large fraction of the sediment was supplied by the Narmada River during ~200–130 ka. Since ~130 ka, clay-dominated sedimentation is attributed to the rise in sea level due to warm and wet climate.